APLIKASI PERSEDIAAN BARANG PADA TOKO RAJAWALI MALANG BERBASIS DESKTOP - Faizah, Fira Isfatul; Sophia, Evy (DINAMIKA DOTCOM, 2016)
Rajawali Store is a business entity engaged in the trade. The store serves the sale of avariety of snacks in wholesale and retail with the aim to meet the needs of the community as wellas small traders around Malang. The purpose of this research is the realization of an application inventory and in order tofacilitate the admin Store Eagles Malang in making the inventory report. The method applied inthis study is developing a system (SDLC) Software Development Life Cycle. Based on the results of tests that have been conducted by researchers, that the applicationinventory on the shop Eagles Malang can facilitate in making the inventory report for thisapplication can obtain the final results of the amount of stock without using a calculator becausethe system that do the calculations. Reports can be printed at any time when needed. The systemcan tell inventory snacks are entering a limited number.Keywords:Â  Application, Inventory, Inventory Application.